2017
DOI: 10.1093/jrr/rrx051
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes of 125I brachytherapy with and without external-beam radiation therapy for localized prostate cancer: results from 300 patients at a single institution in Japan

Abstract: The aim of this study was to determine the outcomes and adverse events for 300 men with prostate cancer treated with 125iodine (125I) brachytherapy with and without external-beam radiation therapy (EBRT) at a single institution in Japan. Between February 2005 and November 2011, 300 consecutive patients with clinically localized prostate cancer were treated with 125I brachytherapy at the Nagoya University Hospital. A total of 271 men were treated with implants with doses of 145 Gy, and 29 men were treated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…Finally, 15 studies were included in the meta-analysis (Fig. 1 ): four prospective cohort studies and 11 retrospective cohort studies [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, 15 studies were included in the meta-analysis (Fig. 1 ): four prospective cohort studies and 11 retrospective cohort studies [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…A meta-analysis of 11 studies [ 16 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 29 ] revealed that the RR of late GI toxic complications from LDR-BT was significantly lower than that from LDR-BT EBRT (3.96; 95% CI, 1.23–12.70; 0.02) (Fig. 2 b).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, SBRT is contraindicated for lesions within 2 cm from the bronchial tree, and a marked prevalence of complications such as pulmonary toxicity and rib toxicity have been reported (24,25). 125 I seed implantation is a minimally invasive treatment for tumors that has been rapidly developed in the past decade and has been listed as a treatment for prostate cancer (26). 125 I seeds are implanted into tumors and continuously generate low-energy gamma-rays to kill tumor cells in a similar manner to multiple hyperfractionated radiotherapy, which can prevent the accelerated repopulation of tumor cells (27,28).…”
Section: Discussionmentioning
confidence: 99%